Magnitude of malnutrition and its associated factors among pediatric cancer patients on chemotherapy at oncology centers in Addis Ababa, Ethiopia, 2024 - Habtamu Wondmagegn Atlaw; Edlework Wondmagegn Atlaw; Biniyam Demisse Andarge; Sayih Mehari Degualem; Tsegazeab Ayele Meshesha; Maycas Gembe; Habtamu Esubalew Bezie (PLoS ONE, 2026)
Background Malnutrition among children and adolescents with cancer in low- and middle income countries significantly contributes to several adverse outcomes which have an impact on health-related quality of life and overall survival. This study aimed to assess the magnitude of malnutrition and its associated factors among pediatric cancer patients on chemotherapy. Methods A health institution-based cross-sectional study was conducted among pediatric cancer patients receiving chemotherapy aged from birth to 15 years attending at Black Lion specialized hospital and Saint Paul’s millennium medical college from May 1 to July 1, 2024. By using a simple random sampling method, 345 participants were selected for face to face interview and anthropometric assessments. Pre-tested semi-structured questionnaire, chart review and anthropometric measurement were used. Variables with p-value <0.25 in the bi-variable logistic regression analysis were entered and checked for association in a multivariable logistic regression model. The level of statistical significance was declared at the p-value < 0.05. Result In this study, we successfully enrolled 320 pediatric cancer patients, which represents a response rate of 92.8% (320/345). The magnitude of malnutrition, defined by low BMI-for-age or weight-for-height/length z-scores, was 28.4% (91/320) (95% CI: 24.8%−31.3% ). Additionally, the prevalence of stunting, based on height-for-age, was 30.6% (98/320) (95% CI: 26.5%–34.2%).Children in the age category of 11–15 years (AOR = 2.54, 95% CI; 1.18–5.48), Children’s of mothers educational level illiterate, (AOR = 2.20, 95%CI; 1.01–4.75), Children form Households which earn <2000 ETB (AOR = 2.93, 95%CI; 1.14–7.53), Children with a cancer duration of 2–4 years (AOR = 1.34, 95%CI; 1.05–1.71), Children with hematologic malignancy (AOR = 2.18, 95%CI; 1.16–3.81), Children who had co-morbidities (AOR = 1.54, 95% CI; 1.12–2.10) and, Children’s who have difficulty of swallowing (AOR = 2.11, 95%CI; 1.22–3.95) were significantly associated factors with being malnourished. Conclusion This study identified malnutrition in 28.4% (91/320) of participants undergoing chemotherapy. Children most at risk were those between 11 and 15 years old, from low-income households, with mothers who had no formal education, Children with a cancer duration of 2–4 years, with hematologic malignancies, with co-morbidities, and with difficulty swallowing.